MANAJEMEN KEUANGAN SEKOLAH DALAM MENDUKUNG PEMBELAJARAN DI SMA LABSCHOOL UNESA 1 SURABAYA - Chimayatul Amanah; Farisa Nuril Hidayah; Abdurrohman Hanifah Al-Fajr; Nabila Az Zahra Dwi Pratiwi; Agus Syaifulloh Akmal; Farah Kamila Ramadhani; Ima Widiyanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of school financial management in supporting the quality of learning. Ineffective financial management, such as lack of transparency, accountability, and weak supervision systems, can impact the effectiveness of budget utilization and educational quality. The purpose of this study is to analyze the implementation of school financial management at SMA Labschool Unesa 1 Surabaya and its impact on improving learning quality. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that school financial management has been implemented systematically through integrated stages of planning, implementation, and supervision. Budget planning is conducted in a participatory manner based on the school’s needs, budget implementation follows established procedures and program priorities, and supervision is carried out periodically with the support of digital systems. The implementation of transparent and accountable financial management has a positive impact on improving learning quality, such as the availability of adequate facilities, enhancement of teachers’ competencies, and the creation of a conducive learning environment. Therefore, effective financial management is a crucial factor in supporting sustainable educational quality.